Agricultural dust explosions in 1999 - Schoeff, Robert W. (Kansas State University. Dept. of Grain Science and Industry, 2010)
There were seven dust explosions reported in the U.S. in 1999 according to Robert W. Schoeff, Professor Emeritus, Kansas State University, and Mavis Rogers, FGIS-USDA. This compares to 18 in 1998, a ten year average of 12.9 explosions, and is the lowest in seven years.
Keywords: Grain dust; Dust explosions